Histomarphology of the Muscle Tissue System (Literature Analysis) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Muscle tissue consists of cells specialized for contraction. Muscles are divided into three types according to their structure and function: skeletal muscle cells, cardiac muscle cells, and smooth muscle cells. Skeletal and cardiac muscle cells are called striated muscle cells because they display alternating rows of striations. In all types of muscles, contraction occurs as a result of the movement of myosin and actin enzymes. Nuclei of muscle cell and muscle fiber are synonymous. Knowing this, we will analyze the literature together.